2016
DOI: 10.1155/2016/4174795
|View full text |Cite
|
Sign up to set email alerts
|

Designing Digital Solutions for Preserving Penan Sign Language: A Reflective Study

Abstract: Oroo’ is a language of nomadic Penans in the rainforests of Borneo and the only way of asynchronous communication between nomadic groups in the forest journey. Like many other indigenous languages, the Oroo’ language is also facing imminent extinction. In this paper, we present the research process and reflections of a multidisciplinary community-based research project on digitalizing and preserving the Oroo’ sign language. As a methodology for project activities, we are employing Participatory Action Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…To our knowledge, message sticks are no longer in active use except among the Punan Batu. For example, a 2016 survey of the rapidly declining knowledge of message stick signs ( oroo’ ) among 80 Penan in the resettlement community of Long Lemai (Sarawak, Figure 1 ), which was created in the 1950s, found that individuals above the age of 50 years knew more than 40 Oroo’ signs, those between 20 and 30 knew eight signs, and individuals under age of 20 knew just four signs (Tariq et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, message sticks are no longer in active use except among the Punan Batu. For example, a 2016 survey of the rapidly declining knowledge of message stick signs ( oroo’ ) among 80 Penan in the resettlement community of Long Lemai (Sarawak, Figure 1 ), which was created in the 1950s, found that individuals above the age of 50 years knew more than 40 Oroo’ signs, those between 20 and 30 knew eight signs, and individuals under age of 20 knew just four signs (Tariq et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the younger generation is more familiar with technology than engaging with their surrounding forest, it is not a reason for the language to continue to be threatened with extinction. There was an initiative by Plimmer et al, (2015) and Zaman et al (2016) in digitizing the language in the form of game applications that are more interactive to the younger generation, namely children as a form of reintroduction to their culture. The game application requires indigenous wisdom from its players.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a research project in Long Lamai was initiated by Universiti Malaysia Sarawak with the community in Baram, one of the biggest and oldest settlements of the Penans on digitalising and preserving the Oroo's sign language. It is aimed to harness indigenous community's tacit and their creative expressions (Zaman et al, 2016;Zaman & Winschiers-theophilus, 2017). It was found that the Penans have their cognitive maps of the jungle which are based on many sources as well as from Oroo' (Zaman, Winschiers-theophilus, et al, 2015) or Omen the signs and directions provided by the birds as pathfinders.…”
Section: Penan's Indigenous Knowledgementioning
confidence: 99%
“…The Namibia University of Science and Technology (NUST) has conducted several long-term community-based design projects (Winschiers-Theophilus et al, 2010) to collect, store, present, and disseminate ICH by digital technology in cooperation with indigenous communities in Namibia, Africa. The Institute of Social Informatics and Technological Innovation (ISITI), Universiti Malaysia Sarawak (UNIMAS), has also launched some co-design projects (Zaman et al, 2016) with indigenous communities in Long Lamai, Malaysia, to explore digital preservation methods for ICH. Kingston University London and the City for Scientific Research and Technological Applications (SRTA-City) in Alexandria, Egypt, jointly organized a summer-school project (Giglitto et al, 2019) and recruited community members from different tribes of Bedouins settled in Borg El-Arab, Alexandria.…”
Section: Community-based Designsmentioning
confidence: 99%